FEATURES OF MANAGEMENT ACCOUNTING AT THE ENTERPRISES OF THE OIL AND GAS INDUSTRY - Z. Korzovatykh (Вестник университета)
This article discusses the features of management accounting at the enterprises of the oil and gas industry, as features of the industry making adjustments in the organization and building a management accounting that are important to any oil and gas company. In the article the analysis of approaches to management accounting in the oil and gas companies, identifies the role of calculation based on activities (ABC) in cost management system on the basis of the process approach. The author justified the proposal for planning purposes and management decisions such signs of classification of expenses as expenses for business processes.